Data Migration Techniques In Cloud Computing With Advanced Encryption Algorithms To Strengthen The Data Security - J.Venkata Krishna, Dr.G.Apparao Naidu, Dr.Niraj Upadhayaya (International Journal of Advanced Science and Technology, 2020)
In recent years so many organizations and IT companies run large applications with huge amount of data to be transferred among cloud centers. It happens because of high demand of data in IT and business sectors. The data migration process facing so many issues in outsourcing of data like backups, security and changes in cloud data centers (cloud storage). At the same time the data transfer rate and the efficiency of the cloud channel will diminished due to low signals and improper usage of migration techniques at cloud centers. Therefore we propose a novel data migration technique with improved encryption algorithms like modified advanced encryption standard (MAES) and honey key encryption. At the same time we provide additional security to the end users with the help of RSA algorithms. The proposed approach aims at strong security and reduces the overheads against data migration. Compared to former approaches the anticipated one took less time for data migration and reduces the cost.